Evaluation of geo-hydrochemical and biological contamination of Massah spring water, Massah city, NE Libya - El-Shawaihdi, H.; El-Seifat, R.M-S; Shaltami , R.; Salloum , M. (Libyan Journal of Science &Technology, 2022)
This work attempts to characterize the chemical and biological characteristics of Massah spring water, NE Libya, with especial emphases on the environmental status of this water. The pH, major ions and TH values are below the permissible limit, while the values of TDS and heavy metals (except for Cu and Zn) are over the acceptable limit of WHO (2011). The MI values indicate that the water is very pure with Cu and Zn (class I) and seriously affected by Pb and Cd (class VI). Important parameters such as RSC, Na%, SAR, MAR, KR and PI, reveal good quality water for irrigation purposes. However, some signs of bacterial contamination of Escherichia coli (E. coli) have been detected when tested in different laboratories. The type of water that predominates in the study area is CaHCO3-type